Esquema instrumental de planificación territorial: Articulación de servicios ecosistémicos del Páramo Miraflores y Gigante, Huila (2024)
This The Páramo Cerro Miraflores, located in the municipality of Gigante in Huila, Colombia, is a high-altitude ecosystem crucial for water regulation, biodiversity conservation, and the provision of essential ecosystem services. This ecosystem faces significant threats from deforestation, intensive agriculture, grazing, and climate change, leading to habitat degradation, biodiversity loss, and disruption of hydrological cycles. In this context, territorial planning emerges as a vital tool to integrate ecosystem services and promote sustainable development in Gigante. This thesis aims to develop an instrumental framework for territorial planning that effectively integrates the ecosystem services of Páramo Cerro Miraflores with the needs and aspirations of the municipality of Gigante. The study involves a comprehensive analysis through various frameworks: theoretical, conceptual, historical, geographical, referential, operational, and diagnostic. The theoretical framework provides a robust foundation for understanding ecosystem services and sustainable territorial planning. The conceptual framework clarifies key terms and their interrelationships, facilitating a shared understanding among stakeholders. The historical framework contextualizes land use evolution and environmental policies in the region. The geographical framework describes the physical characteristics of the páramo, highlighting areas for conservation and ecological restoration.